2009
DOI: 10.1002/ibd.20604
|View full text |Cite
|
Sign up to set email alerts
|

Development of extraintestinal manifestations in pediatric patients with inflammatory bowel disease

Abstract: Background-Extraintestinal manifestations (EIMs) in pediatric patients with inflammatory bowel disease (IBD) are poorly characterized. We examined the prevalence of EIMs at diagnosis, subsequent incidence, and risk factors for EIMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
166
5
21

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(203 citation statements)
references
References 29 publications
11
166
5
21
Order By: Relevance
“…The ASAS criteria employ both of these features to classify spondyloarthritis, and hence a higher rate of spondyloarthritis was detected in our UC cohort. This finding is in contrast to the current literature that suggests a lower rate of spondyloarthritis in UC compared to Crohn's disease (1,4,5). Since active joint symptoms are generally reported to be more frequent in active UC compared to active Crohn's disease, it is possible that more patients with active UC were presenting for evaluation and were concomitantly diagnosed with arthritis.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The ASAS criteria employ both of these features to classify spondyloarthritis, and hence a higher rate of spondyloarthritis was detected in our UC cohort. This finding is in contrast to the current literature that suggests a lower rate of spondyloarthritis in UC compared to Crohn's disease (1,4,5). Since active joint symptoms are generally reported to be more frequent in active UC compared to active Crohn's disease, it is possible that more patients with active UC were presenting for evaluation and were concomitantly diagnosed with arthritis.…”
Section: Discussioncontrasting
confidence: 80%
“…UC has been associated with a lower prevalence of arthropathy in the literature when compared to Crohn's disease (1,(4)(5)(6), although others have reported that there is no major difference in the occurrence of spondyloarthritis between UC and Crohn's disease (7). Axial arthropathies, which include sacroiliitis and spondylitis, have been estimated to occur in 5-22% of patients with Crohn's disease and 2-6% of patients with UC.…”
Section: Introductionmentioning
confidence: 99%
“…Extraintestinal manifestations in IBD can affect the skin, eyes, musculoskeletal and hepatobiliary systems. 13 Once IBD is suspected, patients should be fast tracked to specialist services (for relevant blood and stool tests see Fell et al 13a and figure 2). The revised Porto criteria provide detailed guidance on the diagnostic evaluation of paediatric patients with IBD 10 emphasising the necessity to perform upper gastrointestinal endoscopy and ileocolonoscopy with histology as well as small bowel imaging (see figure 1).…”
Section: Diagnosismentioning
confidence: 99%
“…39 Older children and adolescents in particular are vulnerable to oral CD manifestations. 40 One of the reasons why it is important to be aware of the signs and symptoms of CD is due to the hypothesis that oral inflammation may precede intestinal manifestation of disease. 41 In a tertiary centre case-control study conducted in Portugal, consisting of 113 patients with previously diagnosed IBD and 58 healthy controls, there was a significantly increased prevalence of oral symptoms when compared with the control that did not have IBD (54.9% vs. 24.3%, P = 0.011).…”
Section: Introductionmentioning
confidence: 99%